2011
DOI: 10.48550/arxiv.1111.2339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SDSS J080434.20+510349.2: Cataclysmic Variable Witnessing the Instability Strip?

E. Pavlenko,
V. Malanushenko,
G. Tovmassian
et al.

Abstract: SDSS J080434.20+510349.2 is the 13th dwarf nova containing a pulsating white dwarf. Among the accreting pulsators that have experienced a dwarf novae outburst, SDSS J0804 has the most dramatic history of events within a short time scale: the 2006 outburst with 11 rebrightenings, series of December 2006 -January 2007 mini-outbursts, the 2010 outburst with 6 rebrightenings. Over 2006-2011, SDSS J080434.20+510349.2 in addition to positive 0.060 d superhumps during the outburst and 1-month post-outburst stage, 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This short recess between superoutbursts is atypical for WZ Sge-type systems. The amplitude of this superoutburst was similar to the previous, but the shape of the light curve was different: the brightness decreased faster and fewer echoes were detected (Pavlenko et al 2011). By December 2011, more than a year after this superoutburst, the brightness of the system fell practically to the quiescence level.…”
Section: Light Curve Variabilitysupporting
confidence: 74%
See 4 more Smart Citations
“…This short recess between superoutbursts is atypical for WZ Sge-type systems. The amplitude of this superoutburst was similar to the previous, but the shape of the light curve was different: the brightness decreased faster and fewer echoes were detected (Pavlenko et al 2011). By December 2011, more than a year after this superoutburst, the brightness of the system fell practically to the quiescence level.…”
Section: Light Curve Variabilitysupporting
confidence: 74%
“…V455 And is a proven intermediate polar. In SDSS0804 a number of high-frequency periods were detected (Pavlenko et al 2011), but none was identified as a spin period so far. X-ray observations are needed to probe the magnetic properties of the white dwarfs in bounce-back candidates to verify the intermediate polar hypothesis.…”
Section: Accretion Disk Structure Of Bounce-back Systemsmentioning
confidence: 95%
See 3 more Smart Citations